Comparison of Different Rectal Cleansing Methods for Reducing Post-Procedural Infectious Complications After Transrectal Ultrasound-Guided Prostate Biopsy - Lee, Jong Eun; Shin, Sang Soo; Kang, Taek Won; Kim, Jin Woong; Heo, Suk Hee; Jeong, Yong Yeon (Urology Journal, 2020)
Purpose: To compare the efficacy of three different rectal cleansing methods for reducing post-procedural infectious complications after transrectal ultrasound (TRUS)-guided prostate biopsy. Materials and Methods: A total of 451 consecutive patients who underwent TRUS-guided prostate biopsy were prospectively included in this study. All patients received targeted antimicrobial prophylaxis and underwent bowel preparation through laxative administration. The patients were divided into three groups on the basis of the method of rectal cleansing immediately before the procedure. Group I patients (n=165) underwent cleansing of the perianal skin using povidone-iodine cotton balls; group II patients (n=116) received an injection of povidone-iodine solution (0.1 g/mL) into the anal and lower rectal canals; and group III patients (n=170) received direct manual cleansing of the mucosal surface of the anus and lower rectum using povidone-iodine cotton balls. The three groups were compared regarding the incidence of post-procedural infectious complications, re-hospitalization rates, and mean length of hospital stay using one-way ANOVA, the Chi-square test, and multiple logistic regression analysis. Results: Post-procedural infectious complications occurred in 21.8%, 11.2%, and 6.5% of groups I, II, and III, respectively (P < .001). The incidence of overall infectious complications was significantly lower in group II (95% CI: 0.232–0.958, OR = 0.472, P = .038) and group III (95% CI: 0.129–0.555, OR = 0.267, P < .001) than in group I. Re-hospitalization rates were 9.7%, 2.6%, and 0.6% in groups I, II, and III, respectively (P < .001). The incidence of re-hospitalization was significantly lower in group II (95% CI: 0.070–0.869, OR = 0.247, P = .029) and group III (95% CI: 0.007–0.421, OR = 0.055, P = .005) than in group I. The mean length of hospital stay was significantly longer in group I than in group III (P = .009). Conclusion: Combined with targeted antimicrobial prophylaxis, direct manual cleansing of the mucosal surface of the anus and lower rectum using povidone-iodine cotton balls was most effective in preventing post-procedural infectious complications among the three different rectal cleansing methods.